2013
DOI: 10.1155/2013/986254
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Platelet Indices in Patients with Neurodegenerative Diseases: Mean Platelet Volume Was Increased in Patients with Parkinson’s Disease

Abstract: Platelets induce chronic inflammation which is a key step in atherosclerosis and may be involved in the progression of neurodegenerative diseases (NDD). We aimed to measure the mean platelet volume (MPV) and platelet count (PLC) in NDD patients. The present study was designed to investigate the platelet function by measuring MPV and PLC in NDD. A total of 182 outpatients with Alzheimer's (AD) or Parkinson's diseases (PD) were included. The control group consisted of 104 healthy subjects. Platelet count was sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 39 publications
4
32
1
2
Order By: Relevance
“…Since platelets present neuron-like metabolic pathways, previous studies have shown that in 15 AD, APP acts as a platelet-membrane receptor contributing mostly to soluble β-amyloid after platelet activation (Bram et al, 2018). Mitochondrial dysfunction, higher content in phosphorylated TDP43, and morphological and structural platelet changes in AD and PD have also been reported (Koçer et al, 2013;Kucheryavykh et al, 2017). Whether miRNA deregulation in platelets promotes neurodegeneration or merely reflects its effects remains to be elucidated.…”
Section: Discussionmentioning
confidence: 72%
“…Since platelets present neuron-like metabolic pathways, previous studies have shown that in 15 AD, APP acts as a platelet-membrane receptor contributing mostly to soluble β-amyloid after platelet activation (Bram et al, 2018). Mitochondrial dysfunction, higher content in phosphorylated TDP43, and morphological and structural platelet changes in AD and PD have also been reported (Koçer et al, 2013;Kucheryavykh et al, 2017). Whether miRNA deregulation in platelets promotes neurodegeneration or merely reflects its effects remains to be elucidated.…”
Section: Discussionmentioning
confidence: 72%
“…An increase in MPV is associated with other platelet activation markers such as thromboxane and β-thromboglobulin ( 13 ). The relationship with MPV and the prognosis of bloodstream infection as inflammatory markers in active pulmonary tuberculosis and Parkinson’s disease has been shown in the literature ( 21 - 23 ). MPV increase is also seen in varicocele patients, as reported in two studies ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 97%
“…47 Interestingly, it has been reported that AD patients have similar platelet counts as age-matched controls, but their platelets are in a more activated state. 48,49 Whether APP/ sAPPs are responsible for the phenotype in our patient cohort is unknown.…”
Section: Org Frommentioning
confidence: 99%